COMERCIO, PESCA Y SAL EN EL CAP DE CERVER (ORIHUELA) EN LA BAJA EDAD MEDIA - José Hinojosa Montalvo (Investigaciones Geográficas)
The port of Cap de Cerver was used, along with that of Guardamar, as an inward and outward route for products from Orihuela’s provincial goverment. Jaime II and his successors in the throne favoured chelped it with various privileges, and its activity was oriented towards trade, fishing and exploita- tion. Wheat was the main exported item, although the yearly vessel movement was scarce. Profits at saltworks were not high either at the end for the Middle Ages. For its defence agsint attacks from pirates and corsairs, it had a tower, maintained by Orihuela, with a keeper in charge of it. A country house and some auxiliary buildings would complete the harbour area complex.